Deep source model for Nevado del Ruiz Volcano, Colombia, constrained by interferometric synthetic aperture radar observations. Issue 12 (24th June 2015) - Lundgren, Paul; Samsonov, Sergey V.; López Velez, Cristian Mauricio; Ordoñez, Milton
Abstract Nevado del Ruiz is part of a large volcano complex in the northern Andes of Colombia. Interferometric synthetic aperture radar observations from the RADARSAT‐2 satellite since 2011 show steady inflation of the volcano since 2012 at 3–4 cm/yr. The broad (>20 km) deformation pattern from both ascending and descending track data constrain source models for either point or spheroidal sources, both located at >14 km beneath the surface (mean elevation 4.2 km) and 10 km SW of Nevado del Ruiz, below nearby Santa Isabel Volcano. Stress change computations for both sources in the context of a compressive regional stress indicate that dikes propagating from the source should become trapped in sills, possibly leading to a more complex pathway to the surface and explaining the significant lateral separation of the source and Nevado del Ruiz Volcano.